Pengaruh Substitusi Pupuk Organik Cair dan Media Tanam terhadap Pertumbuhan dan Produksi Kangkung (Ipomoea aquatica) dengan Sistem Hidroponik - Putri, Rona Herlina Rahma; Purbajanti, Endang Dwi; Fuskhah, Eny (Universitas Lampung, 2024)
The growth and production of hydroponic water spinach using liquid organic fertilizer and appropriate planting media determines the success of the plant. The aim of this research is to determine the effect of liquid organic fertilizer (LOF) substitution types and planting media on the growth of water spinach (Ipomoea reptans) production. Data collection was carried out in the month 23 Februaty – 30 March 2023 in Pudakpayung village, Banyumanik District, Semarang City. Treatments were arranged using a completely randomized design with 2 factors. Factor 1 is the planting medium in 2 level, M1 = Rockwool dan M2 = Cocopeat, and factor 2 is the substitution of liquid organic fertilizer in 4 levels, N1 = 4 ml/l AB mix, N2 = 3 ml/l AB mix + 2 ml/l POC, N3 = 2 ml/l AB mix + 3 ml/l POC, dan N4 = 4 ml/l POC. Each treatment was carried out in 3 repetitions so that there were 24 experimental units. The parameters observed were plant height, number of leaves, root length, shoot fresh weight, root weight, biomass weight, and leaf color. The data was analyzed for variance and further tested using the honest real difference (BNJ) at the 5% level. The research results showed that the use of LOF of rice waste and papaya fruit could substitute AB mix at a concertation of 2 ml/l AB mix + 3 ml/l LOF or 50%. However, the use of 100% POC cannot replace AB mix in growth and production of water spinach. Keywords : AB mix, cocopeat, liquid fertilizer, rockwool, rice, papaya fruit, waste